THE STUDY OF GENDER ON LANGUAGE USE THROUGH CONVERSATION OF XI SOCIAL 1 STUDENTS AT SMAN 9 MUSI RAWAS - Anggraini, Liza; MAISARAH, IRA; SYAFRYADIN, SYAFRYADIN; ARSYAD, SAFNIL (Universitas Islam Negeri (UIN) Fatmawati Sukarno Bengkulu, 2022)
The focus of this research is a sociolinguistic examination of the impact of gender on language use. The primary goal of this research is to analyze the implications of men's and women's roles on their language usage. This research aims to highlight the variables that contribute to disparities in how gender impacts language use. This study's inquiry method is a questionnaire and audio-recoding. This study has shown differences in how men and women use language in our society and others like it. They use only some of the same forms; instead, they use different quantities or frequencies of the same form. In a society where gender plays a significant role, language is essential in contributing to that role. Gender roles, men's and women's identities, the hierarchical nature of gender relations, and men's dominance are all factors that contribute to differences in language use. Gender differentiation does not exist in a vacuum; it interacts with other types of social differentiation in a complex way. Language and gender, on the other hand, are formed through participation in everyday social activities. In conclusion, gender and language are inextricably linked.